Mechanism of BCDX2-mediated RAD51 nucleation on short ssDNA stretches and fork DNA - Akita, Masaki; Girvan, Paul; Spirek, Mario; Novacek, Jiri; Rueda, David; Prokop, Zbynek; Krejci, Lumir (Nucleic acids research, 2024)
Homologous recombination (HR) factors are crucial for DSB repair and processing stalled replication forks. RAD51 paralogs, including RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3, have emerged as essential tumour suppressors, forming two subcomplexes, BCDX2 and CX3. Mutations in these genes are associated with cancer susceptibility and Fanconi anaemia, yet their biochemical activities remain unclear. This study reveals a linear arrangement of BCDX2 subunits compared to the RAD51 ring. BCDX2 shows a strong affinity towards single-stranded DNA (ssDNA) via unique binding mechanism compared to RAD51, and a contribution of DX2 subunits in binding branched DNA substrates. We demonstrate that BCDX2 facilitates RAD51 loading on ssDNA by suppressing the cooperative requirement of RAD51 binding to DNA and stabilizing the filament. Notably, BCDX2 also promotes RAD51 loading on short ssDNA and reversed replication fork substrates. Moreover, while mutants defective in ssDNA binding retain the ability to bind branched DNA substrates, they still facilitate RAD51 loading onto reversed replication forks. Our study provides mechanistic insights into how the BCDX2 complex stimulates the formation of BRCA2-independent RAD51 filaments on short stretches of ssDNA present at ssDNA gaps or stalled replication forks, highlighting its role in genome maintenance and DNA repair.
Keywords: DNA Replication; Mutation; Humans; DNA-Binding Proteins; multiproteinové komplexy; Rad51 Recombinase; DNA, Single-Stranded; jednovláknová DNA; DNA vazebné proteiny; vazba proteinů; rekombinasa Rad51; Protein Binding; mutace; Multiprotein Complexes; replikace DNA; lidé